Etanercept – review of efficacy and safety after five years of clinical use. Issue 1 (1st September 2004) - Fleischmann, Roy; Stern, Richard; Iqbal, Imran
Etanercept (Enbrel ®, Immunex corporation) was approved for use in rheumatoid arthritis 5 years ago for the treatment of patients with an incomplete response to methotrexate or disease-modifying antirheumatic drug failures and has since been approved for patients with early rheumatoid arthritis (including treatment-naïve patients), polyarticular course juvenile rheumatoid arthritis, psoriatic arthritis and ankylosing spondylitis. Etanercept has a dramatic effect on the clinical symptoms of disease and significantly retards x-ray progression in rheumatoid arthritis and in many patients, halts progression. The safety profile has been demonstrated to be relatively benign although there are specific safety issues which require continuing surveillance, including serious bacterial and opportunistic infections and the question as to whether there is an increased risk of lymphomas with continued use.